2016
DOI: 10.1200/jop.2015.008920
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Clinical Trial–Associated Workload in Community-Based Research Programs Using the ASCO Clinical Trial Workload Assessment Tool

Abstract: QUESTION ASKED:Recognizing that it is a challenge for clinical research managers to determine appropriate workload for research staff, we asked if the ASCO Clinical Trial Workload Assessment Tool is helpful at gauging protocol-specific complexity and workload effort for clinical trials across multiple practice settings. SUMMARY ANSWER:The majority of 51 participating research programs (96%) were able to provide at least 5 months of data. This response rate, along with feedback received from the participants, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…ASCO has done substantial work to further this vision, including developing guidance, tools, and resources for improving clinical trial feasibility assessments, internal quality assurance, and contract negotiations, centralizing coverage analyses to improve clinical trial billing compliance, assessing staffing and workload needs, and streamlining serious adverse events reporting. [31][32][33][34][35][36][37][38] During the COVID-19 pandemic, regulators, sponsors, and CROs quickly implemented new policies and guidance that reduced administrative and regulatory requirements. 1,8 Policies that should continue include allowing virtual, efficient, and flexible options for site selection, study start up Additionally, the pandemic demonstrated the importance of information technology to improved efficiency of trial administration and communications.…”
Section: Goal 2: Design More Pragmatic and Efficient Clinical Trialsmentioning
confidence: 99%
“…ASCO has done substantial work to further this vision, including developing guidance, tools, and resources for improving clinical trial feasibility assessments, internal quality assurance, and contract negotiations, centralizing coverage analyses to improve clinical trial billing compliance, assessing staffing and workload needs, and streamlining serious adverse events reporting. [31][32][33][34][35][36][37][38] During the COVID-19 pandemic, regulators, sponsors, and CROs quickly implemented new policies and guidance that reduced administrative and regulatory requirements. 1,8 Policies that should continue include allowing virtual, efficient, and flexible options for site selection, study start up Additionally, the pandemic demonstrated the importance of information technology to improved efficiency of trial administration and communications.…”
Section: Goal 2: Design More Pragmatic and Efficient Clinical Trialsmentioning
confidence: 99%
“…Difficulty with the concept of randomisation is a recognised factor affecting accrual to CCTs [ 15 , 24 , 25 , 26 , 27 ]. Understanding and acceptability of clinical equipoise is important in determining whether patients consent to randomisation and accept the treatment allocation assigned to them [ 28 ]. In our study, 58% of patients and 60% of previous CCT participants had a “therapeutic misconception” [ 29 ], despite 87% of previous CCT participants reportedly understanding the trial explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Four of seven sites used an acuity index to assign studies so that no single employee had the majority of complex studies. These indices are algorithms that quantify coordinator/nurse workload on a study . Although SOPs, structure modifications, and acuity measures assisted in staff performance, the single most important factor was the experience and direct supervisory role of the physician leader and research manager.…”
Section: Discussionmentioning
confidence: 99%